Natural amenities and the spatial distribution of Swiss income - Joséphine Leuba (University of Neuchâtel, Institute of Economic Research (IRENE), 2019)
The present article describes how the spatial distribution of income in Switzerland is related to natural amenities. We explore the link between inequalities in Swiss municipalities and the presence of lakes, rivers, mountains, good accessibility and green amenities. By using fiscal data on average income, Gini index and density of taxpayers in different income brackets, we confirm that a larger variety of landscape is associated with larger spatial income differentials. We also show that inequalities are more pronounced within municipalities located in a particularly nice environment.
Keywords: D30; J31; J61; R12; R23; 330; spatial income distribution; natural amenities; income sorting; inequality